Notices of (1) A Bronze Socketed Axe from Daviot, Aberdeenshire, and (2) A Stone Mould for Casting Whorls, from Insch, Aberdeenshire, with (3) Notes on Lead Whorls, Lead Brooches, and Button Moulds (Proceedings of the Society of Antiquaries of Scotland, 1913)
The axe, which was found in the vicinity of an earlier discovery of a bronze sword, is a well-preserved example of the socketed and looped variety. The objects are broadly contemporary and could have been deposited together. The stone mould was an isolated find. A very fine button mould with an inscription dated 1659 is described in detail.